'A City's Paradise': preserving the remainder of Box Hill, voluntary social action and Country Life, 1919–1936. (2nd January 2022) - Grieves, Keith
ABSTRACT: Land was first purchased at Box Hill, Surrey, on the North Downs, to save a famous viewpoint in 1914. Safeguarding the remainder of Box Hill from development necessitated public appeals in 1919, 1923, 1926 and 1935. Led by the largely autonomous Box Hill Management Committee, and often supported by Country Life, voluntary social action in Surrey and London was mobilised to preserve adjoining land for the National Trust by accretion, intent on avoiding spoliation by villas on winding drives, extensive tree felling, streets of bungalows, and highway construction. Sub-national piecemeal protection and voluntary vigilance sustained delight in the country by subscribers who affirmed their familiarity with Box Hill, where views, trees and sequestered spaces on low and high ground offered quiet enjoyment amid common nature. Using sources which originated in the hill's management, complemented by Country Life and newspaper reports, the article evaluates the interrelationship of locality and nation during the subscription appeals, with reference to private acts of informal benevolence and personal sense-impressions of Box Hill. The importance of providing respite from congested districts, on unembellished former wooded pasture in its natural state, is explored before sufficient national political consensus arose for the statutory protection of open country. In 1944 the Greater London Plan demanded that remaining unspoiled chalk country should be taken into public possession.